Polityka społeczna wobec rodzin wielodzietnych - Woś, Jerzy (Wydział Prawa i Administracji UAM, 1985)
Irrespective of the present controversies related to numerous families, the system of social assistance rendered to them should undergo substantial modifications. In the centralized State system the effectiveness of compensating for the increase of maintenance costs has to be advanced and the concentration of resources must be carried out by means of giving up assisitance to well-to-do families. The enterprises though, should talee more account to workers' attitudes in the employed members of families, including the numerous ones. The social functions of State and enterprises must result from a complex system of social assistance.
Social policies towards numerous families